2007
DOI: 10.1177/030089160709300611
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Survival in Breast Cancer Patients following Bone Metastasis

Abstract: In the result of study, for patients with breast cancer, survival following bone metastasis is affected by secondary prognostic factors such as disease-free interval and extent of metastasis besides primary prognostic factors related to the primary tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
1
21
2
Order By: Relevance
“…According to our data, these primary sites constitute 74.6% cases out of a total of 114 cases with known primary. A slight difference in the pattern of metastatic bone disease which we found was that lung, thyroid and kidney cancer implants in bone are less common and secondary bone involvement by ovarian and gastrointestinal cancers is more common as compared to international data available (Berruti et al, 2000;Yavas et al, 2007).…”
Section: Discussioncontrasting
confidence: 66%
“…According to our data, these primary sites constitute 74.6% cases out of a total of 114 cases with known primary. A slight difference in the pattern of metastatic bone disease which we found was that lung, thyroid and kidney cancer implants in bone are less common and secondary bone involvement by ovarian and gastrointestinal cancers is more common as compared to international data available (Berruti et al, 2000;Yavas et al, 2007).…”
Section: Discussioncontrasting
confidence: 66%
“…Recently, a retrospective observational study showed that the median overall survival after diagnosis of prostate cancer with spinal metastases was 24 months with an estimated 1-year overall survival of 73 % [9]. The median survival time after diagnosis of breast cancer with bone metastases was 32 months [10].…”
Section: Prognosismentioning
confidence: 99%
“…Among women with bone metastases from breast cancer, median survival is approximately 2 to 3 years (8), in comparison with the 12-to 18-month median survival in patients with liver metastases (9). Unfortunately, specific prognostic models for long-term survival in patients with bone metastases from breast cancer are not well developed (10)(11)(12)(13)(14). We have previously shown that elevated baseline levels of the biochemical marker N-telopeptide of type I collagen (NTX) were associated with an increased risk of SREs (15,16), and normalization of NTX levels correlated with reduced risks of fracture, SREs, and death versus persistently elevated NTX after 3 months of treatment with zoledronic acid (ZOL; refs.…”
Section: Introductionmentioning
confidence: 99%